2010
DOI: 10.1007/s11274-010-0599-9
|View full text |Cite
|
Sign up to set email alerts
|

Heat and phosphate starvation effects on the proteome, morphology and chemical composition of the biomining bacteria Acidithiobacillus ferrooxidans

Abstract: Acidithiobacillus ferrooxidans is a Gram negative, acidophilic, chemolithoautotrophic bacterium that plays an important role in metal bioleaching. During bioleaching, the cells are subjected to changes in the growth temperature and nutrients starvation. The aim of this study was to gather information about the response of the A.ferrooxidans Brazilian strain LR to K2HPO4 starvation and heat stress through investigation of cellular morphology, chemical composition and differential proteome. The scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Moreover, confocal microscopic data unveiled the fact that in low phosphate conditions, the cells were more elongated as compared to cells grown under normal phosphate conditions. This is concordant with what observed in other bacteria like M. tuberculosis (Rifat et al, 2009), Acidithiobacillus ferrooxidans (Ribeiro et al, 2011), Staphylococcus aureus (Watson et al, 1998), Vibrio cholerae (Holmquist and Kjelleberg, 1993), where cell elongation under phosphate limitation was found to be a strategy to meet their phosphate demand by increasing the surface to volume ratio (Young, 2006). Further studies also revealed that phosphate starved B. anthracis, become more tolerant toward replication and translation inhibitors.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, confocal microscopic data unveiled the fact that in low phosphate conditions, the cells were more elongated as compared to cells grown under normal phosphate conditions. This is concordant with what observed in other bacteria like M. tuberculosis (Rifat et al, 2009), Acidithiobacillus ferrooxidans (Ribeiro et al, 2011), Staphylococcus aureus (Watson et al, 1998), Vibrio cholerae (Holmquist and Kjelleberg, 1993), where cell elongation under phosphate limitation was found to be a strategy to meet their phosphate demand by increasing the surface to volume ratio (Young, 2006). Further studies also revealed that phosphate starved B. anthracis, become more tolerant toward replication and translation inhibitors.…”
Section: Discussionsupporting
confidence: 87%
“…prosperus T was cultured in high salt conditions; and a serine protease, DO/DeqQ family protein (2.0 fold) that has a chaperone function and also has a higher concentration in the At. ferrooxidans response to heat stress (Ribeiro et al, 2011). Finally, the major outer membrane protein 40 had 1.8 fold lower concentration in high salt conditions, potentially to reduce the influx of chloride (Csonka and Hanson, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…remains unclear. Several proteomic studies of A. ferrooxidans have been already performed to characterize protein expression under different environmental conditions including phosphate starvation (Jerez et al 1992), pH perturbations (Amaro et al 1991), copper and other heavy metals exposure (Novo et al 2000), oxidation of metal sulfides, thiosulfate, elemental sulfur and ferrous iron (Bouchal et al 2006;Chi et al 2007;He et al 2005;Ramirez et al 2004), and recently temperature adaptation (Mykytczuk et al 2011;Ribeiro et al 2011). Ohmura et al (2002) purified significant amounts of an acid-stable 28-kDa monomer c-type cytochrome under anaerobic conditions in A. ferrooxidans strain JCM 7811.…”
Section: Introductionmentioning
confidence: 99%